Locals versus foreigners’ emotion-motivational responses towards traditional food and non-traditional food - Rita, P.; Arriaga, P.; Moura, A.; Guerreiro, J. (Spanish Journal of Marketing - ESIC, 2023)
Purpose: The purpose of this paper was to study responses to traditional food of a country, focusing on emotion-motivational responses by locals and foreigners. Design/methodology/approach: Through an experimental design study, Portuguese and Foreign participants were exposed to both traditional and nontraditional food pictures of a country and asked to evaluate their emotional and motivational responses while physiological responses of electrodermal activity were continuously recorded. Predisposition factors of body dissatisfaction, food neophobia, and food involvement were also evaluated given their potential role in predicting the responses to the visualization of the food pictures. Findings: This study found that local traditional food received a higher positive evaluation than nontraditional food with locals evaluating it even higher than foreigners. Higher feelings of arousal and desire as well as willingness to try in response to traditional food were also found as well as higher feelings of pleasure by locals. However, interestingly, and contrary to expectations derived from previous literature, emotion-motivational responses were not significantly different between locals and foreigners. Originality/value: To the best of the authors’ knowledge, this research addressed an identified research gap in the literature, being the first one evaluating the autonomic responses of consumers to traditional food by exploring how local and foreign consumers respond to traditional food versus nontraditional food using psychophysiological measures of emotion.